Hubungan Pelayanan Prima, Tarif Pelayanan Dan Fasilitas Dengan Kepuasan Pasien Rawat Jalan Umum Di Rumah Sakit Hermina Mekarsari: The Relationship between Excellent Service, Service Rates and Facilities and General Outpatient Satisfaction at Hermina Mekarsari Hospital - Lestari, Antin Widya (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: Outpatient satisfaction is one of the indicators to measure the success of a service provided the achievement of outpatient satisfaction at Hermina Mekarsari Hospital.This study aims to determine the relationship between excellent service, service rates and facilities with general outpatient patient satisfaction at Hermina Mekarsari Hospital in 2023. Methods: This research is a quantitative study with a cross-sectional design. The sample in this study were general outpatients at Hermina Mekarsari Hospital in February-March. The sampling technique used was purposive sampling with a sample size of 131 respondents. The instrument used in this study was a questionnaire. Results: This research show that 90 (68,7%) respondents were satisfied with the services provided; 75 (57,3%) respondents thought that the general outpatient of Hermina Mekarsari Hospital provided excellent service; 77 (58,8%) respondents thought that the service rates in the general outpatient of Hermina Mekarsari Hospital were appropriate and more than half  namely 72 (55%) respondents thought that the facilities in the outpatient of Hermina Mekarsari Hospital were complete. There is a relationship between excellent service (p-value = 0,002); service rates (p-value = 0,004) and facilities (p-value = 0,008) with patient satisfaction. Discussion: There is a relationship between excellent service, service rates and facilities with general outpatient patient satisfaction at Hermina Mekarsari Hospital.